The Effectiveness of Audiovisual Media and Fairytale on The Level of Anxiety in Toddler during Immunization - Hariastuti, Fela Putri; Kasmini Handayani, Oktia Woro; Raffy Rustiana, Eunike (Universitas Negeri Semarang, 2020)
Anxiety during immunization is a response shown by toddler during the treatment and it is indicated through mood disorder, that is deep and continually dreadful or worry feelings. The anxiety on the toddler must be overcome well, because it can influence his/her future development, and one way to overcome the anxiety on the toddler is giving media distraction through fairytale reading and audiovisual. The purpose of this research is to know the differences between giving the audiovisual media and the fairytale towards the anxiety level on the toddler during immunization. The research design uses Quasi-Experimental with Two Group Pre-Post Test Design, and the total sample is 94 respondents and they were taken by using consecutive sampling method. The data collection technique uses questionnaire, and in order to analyze the data, this research uses Ã¢â‚¬ËœWicoxonÃ¢â‚¬â„¢ and Ã¢â‚¬ËœMann WhitneyÃ¢â‚¬â„¢ statistic tests. The results of this research were, it was found that the counseling by giving the fairytale reading method was little bit more effective than the audiovisual media, with Mean Rank score of the audiovisual was 51.50 and Mean Rank of the fairytale was 43.50, and the Significance value was 0.026 which was smaller than the significance level ÃÂ <0.05. These two counseling methods could be used to decrease the anxiety level on the toddler during immunization. According to the results above, the average score of giving the fairytale reading was more effective than giving the audiovisual media. It was caused by the distraction effect which was experienced by the toddler during his/her interaction with the fairytale reader was stronger, so it could decrease his/her anxiety level.